Use of compost from olive oil by-products as soil amendment: effect on physical and chemical properties of loamy-sand soils - Bueno Grimalt, Luis Anibal (2014)
Compost obtained from olive oil by-products are usually characterized byhigh potassium (K) and phosphorous (P) content as well as moderate to high electrical conductivity (EC) levels. Amending soils with compost may represent an interesting option for restoring nutrients; nevertheless depending on soil characteristics amending it with a given compost may either produce a benefit or lead to undesirable effects. The aim of this work was to evaluate dynamics of both chemical and physical parameters in soils amended with compost obtained from olive oil by-products. For that purpose, plastic pots were filled with loamy-sand soil samples with or without the addition of compost (150 t ha-1), disposed under irrigation and collected after 30, 90 and 180 days for analysis. Results showed that bulk density (BD) was not affected by compost application, however, hydraulic conductivity was greatly reduced. Regarding to chemical parameters, contents of organic matter (OM), nitrogen (N), available P and available K were higher in amended soils than in control soils. Finally, EC was markedly increased at initial time, however, it decreased to normal levels 30 days after amendment. Together the results suggest that amending soils with compost obtained from olive oil by-products may represent an interesting option to recycle olive oil by-products, improving soil properties and decreasing the utilization of chemical synthesis fertilizers.